RESEARCH ON HEAT DISSIPATION OF LTCC SUBSTRATE MICROCHANNEL BASED ON ORTHOGONAL DESIGN - HE Wei; HUANG ChunYue; LIANG Ying (Jixie qiangdu)
The establishment of micro channel LTCC（Low-temperature cofired ceramics, LTCC） substrate finite element analysis model of multi chip module and the thermal simulation analysis on it. The effect of different microchannel structures, microchannel diameter and fluid flow velocity on the heat dissipation performance was analyzed,Using orthogonal table design, nine multi-chip module models with different combinations of structural parameters were designed. Nine sets of temperature data were obtained and range analysis and variance analysis,The results show that the order of influencing factors on the heat dissipation performance is as follows: microfluidic structure, microfluidic channel diameter and fluid flow rate. When the confidence level is 90%, the micro channel structure and the micro channel diameter have a significant effect on the heat dissipation of the micro channel, and the flow velocity has little effect on the heat dissipation of the micro channel.